Optimizing the “Kawan Belajar” Learning Community to Enhance Teacher Collaboration at SMP Negeri 4 Pahae Julu - Pardomuan Simanullang; Astriani Sipayung; Indrawaty Gultom; Herawati Nainggolan; Hendra Wanri Lumbangaol (Jurnal Multidisiplin Sahombu, 2026)
The transformation of education in the modern era requires the enhancement of teacher professionalism through innovative and student-centered collaboration. This study aims to examine in depth the implementation of learning communities, the forms of teacher collaboration, and the optimization strategies of learning communities in improving teacher collaboration at SMP Negeri 4 Pahae Julu. This research employs a descriptive qualitative approach to comprehensively describe the phenomenon based on real conditions in the field. Data were collected through observation, interviews, and documentation, with research subjects selected using purposive sampling, including the principal, the learning community coordinator, and teachers. The findings indicate that the learning community “Kawan Belajar” (KaBel) at SMP Negeri 4 Pahae Julu has been implemented regularly, systematically, and sustainably. Its implementation emphasizes a dialogic atmosphere that enables teachers to share experiences, discuss challenges, and collectively reflect on their teaching practices. Teacher collaboration is clearly reflected in joint planning, implementation, and evaluation of learning activities. The optimization of the learning community is supported by the strategic leadership of the principal as a facilitator, the active commitment of teachers, the utilization of digital technology, and periodic evaluation mechanisms. In conclusion, the “KaBel” learning community has proven to be an effective platform for fostering a collaborative and innovative learning culture, enhancing teachers’ professional capacity, and improving the quality of learning in schools, in line with the spirit of implementing the Merdeka Curriculum.